Aeolian proceses as Dust Storms in the Deserts of Central Asia and Kazakhstan - Isanova, Gulnura; Abuduwaili, Jilili (Springer, 2017)
This book highlights the aeolian processes in the desert zone of Kazakhstan and analyzes the current status of dust and sand storms in Central Asia and Kazakhstan. It also highlights the analyses, dynamics and long-term observations of storms on the basis of numerous cartographic materials and satellite images. Dust/sand storms are a common and important phenomenon in the arid and semi-arid regions of Kazakhstan, especially in its southern parts, where areas are covered by a great variety of deserts and offer a significant source of mineral and salt aerosols. The deserts of Kazakhstan mostly cover lowlands and extend from the eastern coast of the Caspian Sea to the piedmonts of the Tien-Shan Mountain. In Kazakhstan, desertification processes due to wind erosion in the form of dust/sand storms were observed in semi-desert and desert landscapes.
Keywords: Eolian processes -- Asia, Central.; Eolian processes -- Kazakhstan.; Central Asia.; Kazakhstan.; elektronické knihy; electronic books